Effect of plasma polarity on the synthesis of graphene quantum dots by atmospheric-pressure microplasmas. (10th September 2020) - Orriere, Thomas; Kurniawan, Darwin; Chang, Yi-Chen; Pai, David Z; Chiang, Wei-Hung
Abstract: The aim of this study is to optimize the production of colloidal graphene quantum dots (GQD) in an aqueous solution containing sodium dodecyl sulfate (SDS) treated by an argon microplasma jet operated in open ambient air. The plasma has been investigated by optical emission spectroscopy and electrical measurements, and the produced GQDs have been studied by Raman spectroscopy, photoluminescence, UV–visible absorption, transmission electron microscopy and atomic force microscopy. We mainly focus on the influence of the polarity of the voltage applied to generate the microplasma. Although the deposited power is higher when using a positive polarity, the energy efficiency is also higher thanks to a faster synthesis rate. To understand the underlying mechanisms, we reproduced the experiments with the addition of H 2 O 2 in the aqueous solution. Results show that the GQD synthesis operates in two steps with SDS fragmentation followed by an electrolysis-related process. We demonstrate that the positive polarity performs better due to higher fragmentation rate.